Multifunctional Zinc Oxide Promotes Electrochemiluminescence of Porphyrin Aggregates for Ultrasensitive Detection of Copper Ion - Han, Qian; Wang, Cun; Li, Zhuozhe; Wu, Jingling; Liu, Ping kun; Mo, Fangjing; Fu, Yingzi (Analytical chemistry (Washington), 2020)
The design and exploration of highly efficient organic luminophores for an electrochemiluminescence (ECL) sensor is a fascinating and promising subject. Herein, we present a surfactant-assisted self-assembly of 5,10,15,20-tetrakis (4-carboxyphenyl) porphyrin (TCPP) J-aggregate as a robust organic luminophore to construct the solid-state ECL sensing platform with significantly enhanced and constantly stable signals, by using peroxydisulfate (S2O8 2–) as the coreactant, and l-cysteine capped zinc oxide nanoflowers (ZnO@Cys NFs) as the multifunctional energy donor and coreactant accelerator. Compared with TCPP monomer, this TCPP J-aggregate possesses a unique aggregation-induced electrochemiluminescence (AIECL) performance, which results in 5-fold enhancement in red-light ECL emission at 675 nm. The resonance energy transfer from the ZnO@Cys NFs (energy donor) to the TCPP J-aggregate (energy acceptor) substantially improves the ECL intensity and stability. ZnO@Cys NFs have also been used as a coreactant accelerator to promote the conversion of more S2O8 2– into SO4 •–. The corresponding ECL mechanism has been investigated by UV–vis absorption spectrum, photoluminescence, ECL, and density functional theory. Since l-cysteine on ZnO@Cys NFs can efficiently realize bidentate chelation with Cu2+, the proposed ECL sensor shows a highly selective and sensitive quenching effect for the detection of Cu2+ with a wide linear range from 1.0 pmol·L–1 to 500 nmol·L–1 and a detection limit of 0.33 pmol·L–1, paving a bright research direction for the development of TCPP aggregates in ECL field.